DWELLING TIME DI PELABUHAN NEW PRIOK CONTAINER TERMINAL ONE ( NCPT1) - Indriyani; Frilia Esti Anggraeni (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2019)
Ports have a good performance using assessments using dwelling time, the performance of the port is expressed well when the container is mean – average stay seven days.The value of the indicator is obtained through secondary data generated by NPCT1 2017. Performance analysis is conducted in accordance with UNCTAD Management Series 2016. From the results of the analysis, the conclusion that NPCT1 performance is good which is between 3 to 4 days and in the future government sets only 2 to 1 day.